Does school type affect cognitive and non-cognitive development in children? Evidence from Australian primary schools - Nghiem, Son; Nguyen, Ha; Connelly, Luke; Khanam, Rasheda (My University, 2015)
This paper investigates the effects of primary school choices on cognitive and non-cognitive development in children using data from the Longitudinal Study of Australian Children (LSAC). We militate against the measurement problems that are associated with individual unobserved heterogeneity by exploiting the richness of LSAC data and applying contemporary econometric approaches. We find that sending children to Catholic or other independent primary schools has no significant effect on their cognitive and non-cognitive outcomes. The literature now has evidence from three different continents that the returns to attending Catholic primary schools are no different than public schools.
Labour Economics
Keywords: Children -- School age; Child Development -- Cognitive; Children -- Outcomes; Education and Training -- Primary; Education and Training -- Educational level; Childhood and child development; Learning, education and training; Education and Training; Children; Child Development; Cognitive; Outcomes; School age; Educational level; Primary; Learning, education and training; Childhood and child development